Molecular weight effect on the behaviors of polystyrene-block-poly(methyl methacrylate) diblock copolymers at air/water interface - Seo, Y; Paeng, K; Park, S (AMER CHEMICAL SOC, 2001)
Diblock copolymer (A-B) behaviors in quasi-two-dimensional space have been examined where the A block is polystyrene (PS) and the B block is poly(methyl methacrylate) (PMMA). The length of the PMMA block was varied while that of the PS block was kept almost the same. The surface pressure isotherms were determined with the aid of a Langmuir film balance. The surface pressure isotherms exhibited two phase transitions attributed to surface micelle formation at low surface pressure and to further assembly of surface micelles at high surface pressure. Atomic force microscope images are correlated with the aggregates of the chains forming the quasi-two-dimensional surface micelles at low surface pressure. Chains having shorter PMMA block than PS block form the micelles with many block copolymer molecules (ca. 430 molecules) whereas chains having 4 times longer PMMA block than PS block form the micelles with several molecules. High compression led the micelles to have a more compact structure. The new structure of crowds of micelles by further compression was observed by a Brewster angle microscope. This does not correspond to big aggregates formation since its structure appearance was reversible whereas the surface micelle formation was irreversible. All the block copolymers used in this study exhibited a hysteresis. In the slow expansion process, the surface pressure of the long chain showed a minimum. Because of the micelle formation in the first cycle of compression and expansion, the hyteresis was remarkably reduced in the consecutive cycles.
Keywords: AIR-WATER-INTERFACE; THIN-FILM BEHAVIOR; POLYSTYRENE MONOMOLECULAR PARTICLES; BREWSTER-ANGLE MICROSCOPY; SURFACE MICELLE FORMATION; POLY(METHYL METHACRYLATES); BLOCK POLYELECTROLYTES; MIXED MONOLAYERS; LIGHT-SCATTERING; GRAFTED POLYMERS